A new species of Traverella Edmunds, 1948 (Ephemeroptera: Leptophlebiidae) from Brazil - Nascimento, Stênio R. S.; Lima, Lucas R. C.; Azevêdo, Carlos A. S. (Zootaxa, 2019)
A new species of Traverella Edmunds (Ephemeroptera: Leptophlebiidae) is described based on male imagoes from the state of Maranhão, northeastern Brazil. The main characteristics that distinguish the new species from the other species are: 1) subgenital plate forming two lateral, broad projections with two fine, long spines dorsally recurved; 2) penis lobe triangular and apically rounded, with a small ventral projection at apex and a ventral longspine slightly curved and directed to midline.